Immunopotentiality of Ayurvedic polyherbal formulations “Saribadi” and “Anantamul Salsa” with augmentation of IgM production and lymphocytes proliferation: A preliminary study - Sarker, Md Moklesur Rahman; Ming, Long Chiau; Sarker, Md Zaidul Islam; Choudhuri, Mohammad Shahabuddin Kabir (Elsevier BV, 2016)
Objective To assess the immunopotentiality of Ayurvedic polyherbal preparations, “Saribadi” and “Anantamul Salsa”. Methods Freshly prepared BALB/c mice splenocytes were cultured with “Saribadi” or “Anantamul Salsa” treatment [doses of 0.25%, 0.50%, 0.75%, 1.00%, 1.50%, 2.00%, 3.00% and 4.00% (v/v)] at 37 °C for 5 days. The immunoglobulin M (IgM) production and lymphocytes proliferation were determined by ELISA and MTT methods, respectively. Endotoxin contamination was assessed by treating the preparations with polymyxin B. Results The doses of “Saribadi” [0.25%, 0.50%, 0.75% and 1.00% (v/v)] significantly increased IgM productions (0.966, 0.728, 0.695 and 0.615 μg/mL vs. control 0.265 μg/mL) and lymphocytes proliferation [absorbance 0.311, 0.394, 0.372 and 0.334 optical density (OD) vs. control 0.162 OD]. Similarly, the doses of “Anantamul Salsa” [0.50%, 0.75%, 1.00% and 1.50% (v/v)] promoted IgM productions (0.933, 0.919, 0.917 and 0.892 μg/mL vs. control 0.502 μg/mL) and the doses of “Anantamul Salsa” [0.50%, 0.75%, 1.00%, 1.50%, 2.00%, and 3.00% (v/v)] stimulated lymphocytes proliferation (absorbance 0.395, 0.326, 0.440, 0.398, 0.452 and 0.355 OD vs. control 0.199 OD). The activity of “Saribadi” and “Anantamul Salsa” was not retarded by the treatment of preparations with polymyxin B. Conclusions Immunomodulatory activity of “Saribadi” and “Anantamul Salsa” was unveiled for the first time. “Saribadi” and “Anantamul Salsa” possess immunostimulating potential acting through the induction of lymphocyte proliferation and IgM production. These preparations may be useful in strengthening immune responses. However, further cellular and in vivo studies are required